Education policies and practices: What have we learnt and the road ahead for Bihar - Priya Ranjan; Nishith Prakash (Institute for the Study of Labor (IZA), 2012)
This paper assesses the status of education, both quantity and quality, in Bihar in both absolute terms and relative to other states in India. It then performs a regression exercise using a panel data of Indian states to identify the correlates of educational outcomes. It also surveys the broader literature on education policies which provides a perspective on the current policies in the field of education in Bihar. Finally, it makes a case for several policy initiatives that should be accorded priority by the policymakers in Bihar.
Keywords: I2; J31; O15; O22; 330; education; enrollment; out-of-school; Bihar; India; Bildungspolitik; Schulbesuch; Bildungsniveau; Bihar; Vergleich; Indien